Effect of Black Cumin and Arjuna Fruit Extract on Lipid Oxidation in Pork Nuggets during Refrigerated Storage - Chauhan, Pranav; Das, Arun K.; Das, Annada; Bhattacharya, Dipanwita; Nanda, P. K. (Journal of Meat Science, 2019)
In this study, the efficacy of arjuna fruit extract (AFE, 1.0 %) and black cumin extract (BCE, 1.5%) in retarding lipid oxidation of pork  nuggets was investigated and compared with a synthetic antioxidant, butylated hydroxytoluene (BHT, 100 ppm) and control sample  during refrigerated storage at 4±1oC for 20 days under aerobic packaging. The total phenolics content of AFE treated cooked pork  nuggets was significantly (p < 0.05) higher compared to control but nuggets with BCE extract had comparable total phenolics with BHT  treated nuggets. However, incorporation of AFE, BCE or BHT did not have any effect on the cooking yield of pork meat nuggets. The  increase in pH during storage was significantly (p>0.05) less in all treated samples as compared to control. The pork nuggets with AFE  had significantly (p
Keywords: Black cumin; Arujna fruit; Meat; Lipid oxidation